Coating on monolithic articles

By adopting a partitioned and layered coating structure in the particulate filter, the problems of low filtration efficiency and backpressure accumulation in the prior art are solved, and the effects of high-efficiency filtration and low backpressure are achieved.

CN119866241APending Publication Date: 2025-04-22JOHNSON MATTHEY PLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380065920.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-28
Filing Date
2023-11-08
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing diesel and gasoline particulate filters are inefficient in the initial use and regeneration process, and are prone to backpressure accumulation, affecting engine performance and fuel economy.

Method used

Coated monolithic products with a partitioned and layered coating structure are used, inorganic oxide coating is used in the front area of ​​the inlet end, and inorganic oxide coating is used in the back area of ​​the outlet end. This structure improves filtration efficiency and reduces back pressure.

Benefits of technology

It achieves the maintenance of high filtration efficiency during initial use and regeneration, while avoiding back pressure accumulation, improving engine performance and fuel economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866241A_ABST
    Figure CN119866241A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a coated monolith article for filtering particulate matter from exhaust gas. The monolith article has an inlet end front region and an outlet end rear region, and includes a zoned and layered coating. The partitioned and layered coating includes an inlet end front region including an inorganic oxide coating and an outlet end rear region including a layered coating, where the lower layer includes a washcoat and the upper layer includes an inorganic oxide coating (e.g., the same inorganic oxide coating as the inlet end front region). The present disclosure also relates to methods of forming the coated monolith articles as described herein and exhaust systems having the coated monolith articles as described herein.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a coated monolithic article for filtering particulate matter from exhaust gas. The monolithic article has an inlet end front region and an outlet end rear region, and includes a partitioned and layered coating. The partitioned and layered coating includes an inlet end front region comprising an inorganic oxide coating and an outlet end rear region comprising a layered coating, wherein the lower layer includes a carrier coating and the upper layer includes an inorganic oxide coating (e.g., the same inorganic oxide coating as the inlet end front region). The present disclosure also relates to a method for forming the coated monolithic article as described herein and an exhaust system having the coated monolithic article as described herein. Background Art

[0002] There are issues regarding the emission of particulate matter (PM), commonly referred to as soot, from internal combustion engines, especially diesel and gasoline engines in automotive applications. The main issues are associated with potential health effects, particularly with very small particles with sizes in the nanometer range.

[0003] Diesel particulate filters (DPF) and gasoline particulate filters (GPF) have been manufactured using a variety of materials (including sintered metals, ceramics or metal fibers, etc.), of which the most common type in actual large-scale production is a wall-flow type made of a porous ceramic material, which is manufactured in the form of a monolithic array of many small channels extending along the length of the body. The alternating channels are blocked at one end, so the exhaust gas is forced to pass through the porous ceramic channel wall, which prevents most of the particles from passing through, so only the filtered gas enters the environment. Ceramic wall-flow filters in commercial production include those made of cordierite, various forms of silicon carbide and aluminum titanate. The actual shape and size of the practical filter on the vehicle and characteristics such as the thickness of the channel wall and its porosity depend on the application of interest. The average size of the pores in the filter channel wall of the ceramic wall-flow filter through which the gas passes is typically in the range of 5μm to 50μm and is typically about 15μm. In stark contrast, most diesel particulate matter from modern passenger car high speed diesel engines is much smaller in size, for example 10 nm to 200 nm.

[0004] Some PM may remain within the pore structure in the filter wall, and this can gradually accumulate in some applications until the pores are bridged by a network of PM, and this PM network then enables easy formation of a particle cake on the inner walls of the filter channels. The particle cake is an excellent filter medium, and its presence provides very high filtration efficiency. In some applications, the soot is continuously burned on the filter as it is deposited, which prevents the particle cake from accumulating on the filter.

[0005] For some filters, such as light-duty diesel particulate filters, it is necessary to periodically remove trapped PM from the filter to prevent the buildup of excessive back pressure, which is detrimental to engine performance and can result in poor fuel economy. Therefore, in diesel applications, retained PM is removed from the filter by burning it in the air in a process during which the amount of available air and the amount of excess fuel used to reach the high temperatures required to ignite the retained PM are very carefully controlled. Towards the end of this process, which is generally referred to as regeneration, the removal of the last remaining particles in the filter can result in a significant reduction in filtration efficiency and the release of a burst of many small particles into the environment. As a result, the filter may have low filtration efficiency when first used and subsequently after each regeneration event and also during the latter part of each regeneration process.

[0006] Thus, it is desirable to improve and / or maintain filtration efficiency at all times—eg, during the early life of a filter when it is first used, and / or during and immediately after regeneration, and / or when the filter is loaded with soot.

[0007] WO2021 / 028691 describes a method for coating a filter comprising a porous substrate having an inlet surface and an outlet surface, wherein the inlet surface is separated from the outlet surface by a porous structure. The filter is coated with a dry powder, which is applied through the inlet face of the filter.

[0008] WO2021 / 165658 describes an apparatus and method for coating a filter, the filter comprising a porous substrate having an inlet surface and an outlet surface. The filter is coated with a dry powder through the inlet surface of the filter, and the dry powder comprises a metal compound for forming a metal oxide by thermal decomposition.

[0009] WO2011 / 151711 describes a method for preparing a filter comprising a porous substrate having an inlet surface and an outlet surface, wherein the inlet surface is separated from the outlet surface by a porous structure containing pores of a first average pore size. The inlet surface comprises a bridging network comprising interconnected refractory material particles on the pores of the porous structure. The method comprises the step of contacting the inlet surface of the filter substrate with an aerosol comprising a refractory material in dry powder form. Summary of the invention

[0010] In a first aspect, the present disclosure provides a coated monolithic article for filtering particulate matter from an exhaust gas.

[0011] The monolithic article has an inlet end front region and an outlet end rear region, and includes a zoned and layered coating, the coating comprising:

[0012] a) an inlet end front region comprising an inorganic oxide coating, and

[0013] b) An outlet end rear zone comprising a layered coating, wherein a lower layer comprises a washcoat layer and an upper layer comprises an inorganic oxide coating layer (eg, the same inorganic oxide coating layer as the inlet end front zone).

[0014] The present invention also relates to a method of forming a coated monolithic article (e.g., a coated monolithic article as described herein), the method comprising:

[0015] i) providing a monolithic product having an inlet end front region and an outlet end rear region,

[0016] ii) applying a washcoat to the outlet end rear region such that the washcoat extends from 50% to 85% of the length of the substrate from the outlet end rear region,

[0017] iii) optionally drying and / or calcining the washcoat.

[0018] iv) applying an inorganic oxide coating to the inlet end front region such that the coating extends from 50% to 100% of the length of the substrate from the inlet end front region.

[0019] In a further aspect, an exhaust system is provided that includes a coated monolithic article (eg, a coated monolithic article as described herein or prepared by a method as described herein), and optionally an internal combustion engine.

[0020] In a further aspect, a method for treating an exhaust gas is provided, the method comprising contacting the exhaust gas with a coated monolithic article (eg, a coated monolithic article as described herein or prepared by a method as described herein).

[0021] Coated monolithic articles as described herein (or prepared by the methods as described herein) have improved properties over prior art coated monolithic articles. For example, coated monolithic articles according to the present invention have improved filtration efficiency without experiencing the increase in back pressure typically associated with improved filtration efficiency. Coated monolithic articles of the present invention have low back pressure and high filtration efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Cold flow back pressure and filtration efficiency are shown for a comparative example and two embodiments according to the present invention.

[0023] Figure 2 Cold flow back pressure and mass loading are shown for a comparative example and two embodiments according to the invention. DETAILED DESCRIPTION

[0024] In a first aspect, the present disclosure provides a coated monolithic article for filtering particulate matter from an exhaust gas.

[0025] The monolithic article has an inlet end front region and an outlet end rear region, and includes a zoned and layered coating, the coating comprising:

[0026] a) an inlet end front region comprising an inorganic oxide coating, and

[0027] b) An outlet end rear zone comprising a layered coating, wherein a lower layer comprises a washcoat layer and an upper layer comprises an inorganic oxide coating layer (eg, the same inorganic oxide coating layer as the inlet end front zone).

[0028] Monolithic products

[0029] A monolithic article as described herein may comprise a plurality of channels for passage of exhaust gas, each channel having a gas contacting surface.Monolithic articles are well known in the art.

[0030] The monolithic article may sometimes be referred to as a substrate, preferably a honeycomb substrate, more preferably a ceramic honeycomb substrate. Such a substrate comprises a plurality of channels adapted for passage of exhaust gases. The channels are parallel and extend from an inlet end (or first end) to an outlet end (or second end), i.e., the channels extend axially through the article. Typically, the channels have a square cross-section, but any known monolithic design may be used.

[0031] The monolithic article / substrate may be formed, for example, from sintered metals, ceramics, or metal fibers, etc. For example, the article may be formed from cordierite, various forms of silicon carbide, or aluminum titanate.

[0032] In some embodiments, the monolithic article is a monolithic filter. It is particularly preferred that the monolithic filter is a wall-flow filter (also referred to as a wall-flow monolithic article). Wall-flow filters are well known, and typically, adjacent channels are alternately blocked at each end of the monolithic article so that, in use, exhaust gases pass along the inlet channel (i.e., the channel that opens at the inlet end of the monolithic article for receiving exhaust gases) and are forced through the channel wall into the adjacent outlet channel (i.e., the channel that opens at the outlet end of the monolithic article).

[0033] The channel walls may have a pore distribution that provides the desired porosity for the monolithic article, the average size of the pores in the channel walls (e.g., filter walls) typically being in the range of 5 μm to 50 μm. Each channel may have a gas contact surface. That is, each channel may have a surface suitable for contacting exhaust gases, for example, when in use. The surface may be provided by the channel wall surface and / or the pores contained therein.

[0034] In another particularly preferred embodiment, the monolithic article is a catalyst article (i.e., a catalytic filter). Catalytic porous monolithic articles are well known and exhibit properties such as oxidation, NO xThe catalyst product can also be selected from, for example, a three-way catalyst (TWC), a NO x Adsorbents, oxidation catalysts, selective reduction catalysts (SCR), hydrocarbon traps and lean NO x catalyst.

[0035] In another particularly preferred embodiment, the monolithic article is a catalyzed wall flow filter. Thus, the article may be, for example, a catalyzed soot filter (CSF), a selective catalytic reduction filter (SCRF), a lean NO x a trap filter (LNTF), a gasoline particulate filter (GPF), an ammonia slip catalyst filter (ASCF), or a combination of two or more thereof (eg, a filter including a selective catalytic reduction (SCR) catalyst and an ammonia slip catalyst (ASC)).

[0036] In another particularly preferred embodiment, the monolithic article is a gasoline particulate filter, which is a catalyzed wall flow filter comprising a TWC catalyst. Generally speaking, the gasoline particulate filter comprises: a platinum group metal selected from the group consisting of Pt, Pd, Rh and mixtures thereof; an oxygen storage capacity (OSC) material; and optionally an inorganic support material.

[0037] The shape and size of the filter (e.g., characteristics such as channel wall thickness and its porosity) can vary depending on the intended application of the filter. The filter can be configured for use with an internal combustion engine to filter exhaust gases emitted by the internal combustion engine. The internal combustion engine can be a gasoline spark ignition engine. However, the filter has specific applications when configured for use with an internal combustion engine in the form of a diesel or gasoline engine.

[0038] The wall-flow filter may be an asymmetric wall-flow filter. Asymmetric wall-flow filter designs are known, for example, from WO2005 / 030365, which discloses a honeycomb filter comprising an array of interconnected porous walls defining an array of first and second channels. The first channel is bounded on its side by the second channel and has a larger hydraulic diameter than the second channel. The first channel has a square cross-section, wherein the corners of the first channel have a shape such that the thickness of the porous wall adjacent to the corner of the first channel is comparable to the thickness of the porous wall adjacent to the edge of the first channel and the second channel. In use, the first channel having the larger hydraulic diameter is oriented to the upstream side. The Society of Automotive Engineers SAE Technical Paper Series 2007-01-0656 explains: "Due to the contraction and expansion of the gas at the inlet and outlet of the filter channels, there is a pressure drop loss in the clean state for the ACT design [for catalytic asymmetric channel technology (ACT) wall-flow filters]. However, when operating on a vehicle, the filter is in a completely clean (fully regenerated) state for very little time." WO2005 / 030365 also explains that the advantages of the asymmetric filter design include an increased effective surface area available for collecting soot and ash particles in the inlet portion of the honeycomb filter, thereby increasing the total storage capacity of the honeycomb filter. The general common sense textbook "Catalytic Air Pollution Control—Commercial Technology", 3rd edition, Ronald M. Heck et al., John Wiley & Co., Hoboken, NJ, USA (2009) pp. 338-340 explains: "This type of [asymmetric filter] channel design achieves a combination of higher ash storage capacity and lower ash loading back pressure due to the larger hydraulic diameter and higher open volume at the inlet. The ACT design also helps to maintain the mechanical and thermal durability of the filter.

[0039] Inorganic oxide coating

[0040] The inorganic oxide coating as described herein may include inorganic particles comprising an aluminosilicate zeolite and a silicone resin.

[0041] The inorganic particles may comprise an aluminosilicate zeolite having a SAR (SAR) greater than 10: 1, greater than 20: 1, greater than 50: 1, greater than 75: 1, or greater than 100: 1. The aluminosilicate zeolite preferably has a SAR greater than 200: 1, more preferably greater than 300: 1, even more preferably greater than 400: 1, and most preferably greater than 500: 1. In some embodiments, the aluminosilicate zeolite has a SAR greater than 1000: 1.

[0042] The aluminosilicate zeolite may have a framework type selected from the group consisting of ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BEC, BIK, BOG, BPH, BRE, CAN, CAS, SCO, CFI, S GF, CGS, CHA, CHI, CLO, CON, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO , FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFR, IFY, IHW, IRN, ISV, ITE, ITH, ITW, IWR, IWW, JBW, KFI, LAU, L EV, LIO, LIT, LOS, LOV, LTA, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, MSO, MTF, MTN, MTT , MTW, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OSI, OSO, OWE, PAR, PAU, PHI, PON, RHO, RON, RRO, R SN, RTE, RTH, RUT, RWR, RWY, SAO, SAS, SAT, SAV, SBE, SBS, SBT, SFE, SFF, SFG, SFH, SFN, SFO, SFW, SGT, SOD, SOS , SSY, STF, STI, STT, TER, THO, TON, TSC, UEI, UFI, UOZ, USI, UTL, VET, WI, VNI, VSV, WIE, WEN, YUG, ZON, or their combination. In some embodiments, the aluminosilicate zeolite may have a framework type selected from the group consisting of AEI, AFT, AFV, AFX, AVL, BEA, CHA, DDR, EAB, EEI, ERI, FAU, FER, IFY, IRN, KFI, LEV, LTA, LTN, MER, MOR, MWF, MFI, NPT, PAU, RHO, RIE, RTH, SAS, SAT, SAV, SFW, TSC, and UFI. In some embodiments, the aluminosilicate zeolite may have a framework type selected from the group consisting of (or consisting of) AEI, BEA, CHA, and MFI. In some embodiments, the aluminosilicate zeolite has a BEA framework type. In some embodiments, the aluminosilicate zeolite has an MFI framework type.

[0043] In addition to the aluminosilicate zeolite, the inorganic particles may include a second zeolite material. Examples of suitable second zeolite materials include silicate zeolites, aluminosilicate zeolites, metal-substituted aluminosilicate zeolites, AlPO, MeAlPO, SAPO, MeAPSO, and the like. The second zeolite material may have a framework type selected from the group consisting of ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFX, AFY, AHT, ANA, APC, APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BEC, BIK, BOG, BPH, BRE, CAN, CAS, SCO, CFI, S GF, CGS, CHA, CHI, CLO, CON, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO , FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU, IFR, IFY, IHW, IRN, ISV, ITE, ITH, ITW, IWR, IWW, JBW, KFI, LAU, L EV, LIO, LIT, LOS, LOV, LTA, LTL, LTN, MAR, MAZ, MEI, MEL, MEP, MER, MFI, MFS, MON, MOR, MOZ, MSO, MTF, MTN, MTT , MTW, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OSI, OSO, OWE, PAR, PAU, PHI, PON, RHO, RON, RRO, R SN, RTE, RTH, RUT, RWR, RWY, SAO, SAS, SAT, SAV, SBE, SBS, SBT, SFE, SFF, SFG, SFH, SFN, SFO, SFW, SGT, SOD, SOS , SSY, STF, STI, STT, TER, THO, TON, TSC, UEI, UFI, UOZ, USI, UTL, VET, WI, VNI, VSV, WIE, WEN, YUG, ZON, or their combination.

[0044] The inorganic particles may include refractory oxide particles, which may be based on an oxide selected from the group comprising (or consisting of) alumina, silica, zirconia, ceria, chromia, magnesia, calcium oxide, titania, and mixed oxides of any two or more thereof. Preferably, the refractory oxide particles include calcium aluminate, fumed alumina, fumed silica, fumed titania, fumed zirconia, fumed ceria, alumina aerogel, silica aerogel, titania aerogel, zirconia aerogel, ceria aerogel or mixtures thereof. The one or more refractory powders (refractory oxide particles) may be produced by a pyrometallurgical process, such as flame pyrolysis.

[0045] The amount of aluminosilicate zeolite present in the inorganic particles can be 10% to 99% by weight, preferably 50% to 99% by weight, more preferably 80% to 99% by weight, and most preferably 90% to 99% by weight. In some embodiments, the inorganic particles comprise (or consist of) aluminosilicate zeolites. In some embodiments, the inorganic particles consist of (or consist of) aluminosilicate zeolites having a SAR greater than 100:1. In some embodiments, the inorganic particles comprise (or consist of) aluminosilicate zeolites having a SAR greater than 200:1. In some embodiments, the inorganic particles comprise (or consist of) aluminosilicate zeolites having a SAR greater than 300:1. In some embodiments, the inorganic particles comprise (or consist of) aluminosilicate zeolites having a SAR greater than 400:1. In some embodiments, the inorganic particles comprise (or consist of) aluminosilicate zeolites having a SAR greater than 500:1. In some embodiments, the inorganic particles comprise (or consist of) aluminosilicate zeolites having a SAR greater than 1000:1.

[0046] Silicone resins are known and are branched cage-like oligo- and polysiloxanes. The branching in silicone resins is due to the presence of so-called "T" and / or "Q" units in the resin, which refer to RSiO, 3 and SiO 4 units (R is alkyl or aryl), wherein the additional silicon units are bonded to oxygen atoms. 3 SiO units) are terminal units in which the oxygen atom provides the connection to the resin backbone. Similarly, the "D" units (i.e., R 2 SiO 2 Units) provide a linear connection across two oxygen atoms. A well-known unbranched and linear polysiloxane is polydimethylsiloxane (PDMS; i.e., (Me 2 SiO) n ).

[0047] Preferably, the silicone resin is solid at room temperature (e.g., about 25°C). Thus, the silicone resin preferably has a melting point greater than 25°C, preferably greater than 30°C, more preferably greater than 35°C. Preferably, the melting point of the silicone resin is less than 100°C, preferably less than 95°C, less than 90°C, less than 85°C or less than 80°C. Unbranched polysiloxanes such as PDMS generally have lower melting points than branched silicone resins. For example, the melting point of PDMS is about -40°C. WO 2011 / 151711 discloses bonding powders in place by treatment with polydimethylsiloxane, which forms silica when hydrolyzed at sufficiently high temperatures.

[0048] Similarly, the inventors have found that it may be preferred that the silicone resin has a glass transition temperature (Tg) greater than 30° C., preferably greater than 35° C., and / or less than 100° C., preferably less than 80° C. Without wishing to be bound by theory, the inventors believe that silicone resins having such melting points and / or glass transition temperatures are particularly suitable for powder coating processes, i.e., for effective dispersion of microparticles along with inorganic particles on a monolithic article, but the melting points and / or glass transition temperatures are low enough to allow low temperature calcination to effectively and efficiently adhere the inorganic particles to the gas contacting surfaces of the channel walls.

[0049] Preferably, the silicone resin has a molecular weight greater than 1,000, preferably greater than 2,000, preferably greater than 5,000, preferably greater than 10,000, and / or a molecular weight less than 500,000, preferably less than 200,000.

[0050] As used herein, molecular weight refers to the weight average molecular weight (M W ), which can be measured using any conventional apparatus in the art. In some embodiments, particularly those embodiments described herein where the silicone resin comprises hydroxyl functional groups, the molecular weight may be relatively low because the hydrogen bonding provided by the hydroxyl functional groups provides the silicone resin with a sufficiently high melting point and / or glass transition temperature. Thus, in some embodiments, the silicone resin may have a molecular weight of 1,000 to 10,000, preferably 1,000 to 5,000, preferably 1,200 to 3,500, such as 1,500 to 2,000. Silicone resins having a molecular weight below 1,000 are less preferred because these silicone resins are generally liquids and are not suitable for dry spraying, or do not have as much branching as larger molecules, which is believed to enhance the bonding of the inorganic particles to the monolithic article.

[0051] However, the molecular weight of the silicone resin can preferably be from 15,000 to 150,000, preferably from 20,000 to 120,000, preferably from 60,000 to 100,000. Some preferred resins have an Mw of from 8,000 to 15,000, some resins are from 20,000 to 60,000, and other resins are from 80,000 to 120,000.

[0052] Particularly preferably, the silicone resin has the formula [R x SiX y O z n , where R is an alkyl or aryl group, X is a functional group bonded to silicon, and where z is greater than 1 and less than 2. As will be understood, n is large in order to provide the oligomers or polymers required for silicone resins, particularly those that are solid at room temperature. Although depending on the molecular weight of the R and X groups, when n is greater than 10, an M W greater than 1,000 can be obtained, when n is greater than 100, an M W greater than 10,000 can be obtained, and when n is greater than 1,000, an M W greater than 100,000 can be obtained. Thus, n can preferably be greater than 10, greater than 100, greater than 1,000.

[0053] As will be understood, R is an alkyl or aryl group bonded to silicon, while X is a non-hydrocarbon functional group bonded to silicon. Similarly, since silicon is a tetravalent atom, it should be understood that x + y + 2z = 4. z is less than 2 because where z = 2, x and y = 0, providing silicon dioxide (i.e., silica; (SiO 2 ) n ). Similarly, z is greater than 1 because where z = 1, x + y = 2, giving a substituted polysiloxane composed of "D" units (e.g., (RXSiO) n ), giving a linear resin (e.g., –O–(SiRX)–O–(SiRX)–O–). An example is polydimethylsiloxane. Thus, O refers to the oxygen that bridges two silicon atoms in the polymer backbone of the silicone resin.

[0054] Preferably, 0 < x + y < 2, preferably 0 < x + y ≤ 1.5, preferably 0 < x + y ≤ 1. Preferably, x, y, and / or x + y are greater than 0.1, preferably greater than 0.2. In a preferred embodiment, x + y is 1, giving a silicone resin commonly referred to as a polyhedral oligomeric silsesquioxane. Preferably, y is less than 1 and / or y is less than x. Even more preferably, 2y ≤ x, preferably 5y ≤ x, preferably 10y ≤ x. In one embodiment, y is 0. For example, y is 0 where the polyhedral oligomeric silsesquioxane is a polyalkylsilsesquioxane, such as polymethylsilsesquioxane (MeSiO 3 / 2 )​n .

[0055] Typically, when present, X is H, hydroxyl (OH), Cl and C 1 –C 6 One or more of the alkoxy groups, preferably OH and C 1 –C 6 One or more of the alkoxy groups, preferably C 1 –C 6 Alkoxy is selected from methoxy (OCH 3 ) and ethoxy (OCH 2 CH 3 In a particularly preferred embodiment, X is one or both of OH and ethoxy. However, X is a functional group, which may also be a reactive functional group, such as an amine group (NH 2 NR 2 ), epoxy, acrylate, and vinyl groups, but these functional groups are less preferred because the presence of hydroxyl or alkoxy groups is believed to provide more effective crosslinking during calcination. As mentioned above, any oxygen present in the terminal functional groups is not effective for the "O" in the above formula. z " has no contribution, the "O z ” refers to silicon bridging oxygen atoms.

[0056] The inventors have discovered that the silicone resins described herein provide coated monolithic articles having the advantageous benefits of enhanced water resistance and improved thermal stability. It has been found that silicone resins are particularly advantageous in bonding inorganic particles to monolithic articles. Without wishing to be bound by theory, the inventors believe that the branched structure and physical properties of the silicone resin allow the resin to first melt during the calcination step as described herein and begin to solidify after bonding (tightly bonding or depositing on) the inorganic particles on the gas contacting surface of the channel. As the resin solidifies, the resin forms additional –Si–O–Si–O–Si– bridges / bonds, further increasing its branched structure. In addition, the inventors believe that such bonding may also be formed with the gas contacting surface (i.e., the monolithic article itself) and the inorganic particles, for example, by forming –Si–O–Al– bonds, further bonding the particles to the appropriate location in the article. As the temperature continues to increase during calcination, the R and X groups are oxidized, leaving behind the silica (SiO 2 ) framework. Therefore, inorganic particles containing silicon and / or aluminum may be preferred, such as zeolites, calcium aluminates, alumina and / or silica.

[0057] Preferably, the silicone resin has a crosslinking degree of greater than 55%, preferably greater than 60%, more preferably greater than 65%, and / or a crosslinking degree of less than 85%, preferably less than 80%.

[0058] As described herein, given the tetravalent nature of silicon, a compound such as x SiX y O z ] n The silicon atoms of the described silicone resins can be in one of four coordination environments, namely, SiO(R / X) 3 、SiO 2 (R / X) 2 、SiO 3 (R / X) or SiO 4 , referred to in the art as "M", "D", "T" and "Q", respectively. Thus, the above formula can be described by aMbDcTdQ, where a+b+c+d=1, and the degree of crosslinking is defined by [(a+2b+3c+4d) / 4]*100. The relative ratio of the number of silicon atoms in each coordination environment can be determined using standard spectroscopic techniques (e.g., multinuclear NMR spectroscopy, especially 29 Si NMR spectroscopy). Alternatively, for commercially available silicone resins, the degree of crosslinking may be provided in the technical data sheet.

[0059] In other words, silicon dioxide (SiO 2 ) is completely composed of "Q"SiO 4 units, where each silicon atom is bonded to four connected oxygen atoms. Thus, in the case where d is 1, this makes the silica 100% cross-linked. On the other hand, by way of example, PDMS is composed entirely of "D" Si(Me) 2 O 2 Formed. Thus, in the case where b is 1, this results in a polydimethylsiloxane having a crosslinking degree of 50%. Thus, the silicone resin preferably has a crosslinking degree between these two extremes and includes a mixture of such units. Thus, the silicone resin may preferably contain (or consist of) MDT units, MTQ units, DTQ units or DT units.

[0060] Preferably, R is C 1 -C 6 One or more of alkyl or phenyl. Due to the oligomeric or polymeric nature of the silicone resin, the number of monomer units is generally large. There may be many cases of two groups, R and X, so that the silicone resin described by a single monomer unit may contain multiple different groups. As described above with respect to the functional group X, X may preferably be both OH and ethoxy. Similarly, R may include more than one C 1 -C 6 Thus, when R is described by more than one group (such as R' and R'), the formula of the silicone resin may be [R' x’ R” x” SiX y Oz ] n , where x'+x"=x. The same applies to the functional group X.

[0061] Preferably, R is one or more of a linear or branched alkyl group and a phenyl group, one or more of a linear alkyl group and a phenyl group, more preferably one or more of a methyl group and a phenyl group. In some preferred embodiments, where R is both a methyl group and a phenyl group, the ratio of phenyl groups to methyl groups is less than 2, preferably less than 1.5, preferably less than 1, preferably less than 0.5. In some embodiments, R is a phenyl group. More preferably, R is a methyl group (i.e., a ratio of 0).

[0062] For the R and X groups, smaller organic groups such as methyl, methoxy and ethoxy are particularly preferred because this increases the SiO 2 content, thereby reducing the weight loss during calcination. In addition, smoke and volatiles (such as H 2 O、CO 2 and other volatile organic compounds).

[0063] Therefore, it is preferred that the silica content of the silicone resin is greater than 50% by weight, preferably greater than 60% by weight, preferably greater than 70% by weight, preferably greater than 80% by weight. The silica content may also be referred to as the ash content, which is the weight of the product (in this case, the product is silica) remaining after complete oxidation, based on the weight of the starting silicone resin. For example, the oxidation may be performed at about 1000°C. Alternatively, the silica content may be obtained from the technical data sheet of a suitable commercially available silicone resin. Alternatively, the silica content may be calculated based on the complete oxidation of silicon to silica and the resin formula. By way of example only, polymethylsilsesquioxane (MeSiO 3 / 2 ) n The silicon dioxide content of polymethylsilsesquioxane is about 2.1*42.7=89.7% by weight (i.e., based on the weight of the silicone resin).

[0064] One particularly preferred silicone resin for use in the process of the present invention is a highly crosslinked ethoxylated poly(dimethylsiloxane) having a silica content of about 82% by weight and a melting point of 35°C to 55°C.

[0065] Preferably, the inorganic particles and / or silicone resin particles have a d value greater than 0.2 μm, preferably greater than 0.5 μm, and / or less than 50 μm, preferably less than 25 μm, preferably less than 20 μm, preferably less than 15 μm, preferably less than 10 μm by volume. 50 .

[0066] Preferably, the total inorganic oxide coating can be applied to the monolithic article at a mass loading of less than 50 g / L, preferably less than 30 g / L. In a preferred embodiment, the total mass loading of the inorganic oxide coating is 1 g / L to 25 g / L, such as 2 g / L to 20 g / L, or preferably 3 g / L to 15 g / L. Preferably, the mass loading of the inorganic particles is at least 1 g / L and / or less than 25 g / L. Preferably, the mass loading of the silicone resin is at least 1 g / L and / or less than 25 g / L. In a preferred embodiment, the mass loading of the inorganic particles is 1 g / L to 15 g / L and / or the mass loading of the silicone resin is 1 g / L to 15 g / L. By way of example, in the case where the weight ratio of the inorganic particles to the silicone resin is 1:1, the loading of the inorganic particles may be 5 g / L, and the loading of the silicone resin may be 5 g / L, so that the total loading of the inorganic oxide coating is 10 g / L. By way of example, in the case of a 2:1 ratio, the inorganic particle loading may be 10 g / L, while the silicone resin loading is 5 g / L, resulting in a total loading of 15 g / L.

[0067] In some embodiments, the ratio of inorganic particles to silicone resin in the inorganic oxide coating is from 0.5:1 to 5:1, preferably from 1:1 to 4:1, such as about 2:1 or 3:1.

[0068] Carrier coating

[0069] The washcoat as described herein may comprise an oxygen storage capacity (OSC) material, an inorganic oxide support, a noble metal, and / or a rheology modifier.

[0070] "Oxygen storage capacity" refers to the ability of a material used as an oxygen storage capacity material in a catalyst to store oxygen under lean conditions and release it under rich conditions.

[0071] Examples of OSC materials that can be used for washcoat include Al 2 O 3 、SiO 2 、TiO 2 、CeO 2 、ZrO 2 、V 2 O 5 ,La 2 O 3 、Nd 2 O3 , Pr 6 O 11 , HfO 2 and zeolites (e.g., zeolites as described herein). In a preferred embodiment, the OSC material present in the carrier coating comprises one or more mixed oxides, such as a mixed oxide of cerium and zirconium, a mixed oxide of cerium, zirconium and aluminum, a mixed oxide of cerium, zirconium and neodymium, a mixed oxide of cerium, zirconium and praseodymium, or a mixed oxide of cerium, zirconium, lanthanum and neodymium. As used herein, the term "mixed oxide" generally refers to a mixture of oxides in a single phase form, as is generally known in the art. In a further preferred embodiment, the carrier coating comprises one or more OSC materials selected from a mixed oxide of cerium and zirconium, a mixed oxide of cerium, zirconium and neodymium, a mixed oxide of cerium, zirconium, lanthanum and neodymium, or a mixed oxide of cerium, zirconium, lanthanum, hafnium and neodymium.

[0072] The amount of OSC material in the washcoat layer may range from 5% to 50% by weight, preferably from 10% to 30% by weight, relative to the total weight of the washcoat layer.

[0073] Examples of inorganic oxide supports can be oxides of Groups 2, 3, 4, 5, 13 and 14 elements. The inorganic oxide support is preferably a refractory oxide that exhibits chemical and physical stability at high temperatures such as those associated with gasoline engine exhaust. The inorganic oxide support can be selected from alumina, silica, titania, and mixed oxides or composite oxides thereof. More preferably, the inorganic oxide support is alumina. In one embodiment, the inorganic oxide support is γ-alumina. The γ-alumina used as the inorganic oxide support preferably has an average particle size of 1 μm to 10 μm, more preferably 2 μm to 8 μm. In another embodiment, the inorganic oxide support is nano alumina. The nano alumina used as the inorganic oxide support preferably has an average particle size of less than 1 μm.

[0074] The inorganic oxide support may be doped with a dopant. The dopant may be selected from La, Sr, Si, Ba, Y, Pr, Nd, Ce and mixtures thereof. Preferably, the dopant is La, Ba, Nd or Ce. Most preferably, the dopant is La or Nd. The dopant content in the inorganic oxide support may be from 1 wt % to 30 wt %, preferably from 2 wt % to 25 wt %, more preferably from 3 wt % to 20 wt %.

[0075] The amount of the inorganic oxide support in the washcoat layer may be 2 to 30 wt %, preferably 5 to 20 wt %, relative to the total weight of the washcoat layer.

[0076] Examples of noble metals that can be used for the washcoat include platinum group metals (such as Ru, Rh, Pt, Os, Ir and Pd), Ag, Au, In, Re, Ge, Be, Ga, Te, Bi and Hg. In a preferred embodiment, the noble metal that can be used for the washcoat is selected from the group consisting of Pt, Pd and Rh.

[0077] The amount of total precious metal in the washcoat may be 0.005 to 10 wt %, preferably 0.001 to 5 wt %, more preferably 0.05 to 3.0 wt %, relative to the total weight of the washcoat.

[0078] Examples of rheology modifiers that can be used in the carrier coating include silanes, amines, acids, polysaccharides (such as starch, cellulose, galactomannan gum, xanthan gum, curdlan, etc.), dispersible cellulose (e.g., Natrosol), TEAOH (tetraethylammonium hydroxide), Dispex, amino acids, β-alanine, and ammonia. In a preferred embodiment, the rheology modifier for the carrier coating is selected from polysaccharides and amino acids, such as Natrosol and β-alanine.

[0079] The washcoat may also contain C 2 -C 6 Aliphatic amino acids. Suitable C 2 -C 6 Aliphatic amino acids include 3-amino-propionic acid, L-alanine, glycine, serine, L-valine, etc. Preferably, C 2 -C 6 Aliphatic amino acids are those with the formula HO 2 C-(CH 2 ) n -NH 2 wherein n is 1 to 5, preferably 1 to 3. A preferred amino acid is 3-amino-propionic acid (n=2).

[0080] Carrier coating C 2 -C 6 The amount of the aliphatic amino acid may be 1 to 50 wt %, preferably 2 to 40 wt %, more preferably 3 to 30 wt % or 5 to 25 wt % relative to the solid mass in the carrier coating.

[0081] The carrier coating may also contain additional components such as metal hydroxides, metal phosphates, metal carbonates or mixtures thereof. The metal hydroxide may be selected from magnesium hydroxide, calcium hydroxide, strontium hydroxide and barium hydroxide. The metal phosphate may be selected from magnesium phosphate, calcium phosphate, strontium phosphate and barium phosphate. The metal carbonate may be selected from magnesium carbonate, calcium carbonate, strontium carbonate and barium carbonate. In a preferred embodiment, the carrier coating comprises barium hydroxide.

[0082] In a preferred embodiment, the washcoat comprises ceria zirconia, alumina, a noble metal selected from Pd, Pt or Rh, barium hydroxide, a rheology modifier and C 2 -C 6 Aliphatic amino acids (eg, 3-aminopropionic acid). The support coating may optionally further comprise lanthanum oxide and / or neodymium oxide.

[0083] Preferably, the total washcoat loading is 35 g / L to 150 g / L, preferably 40 g / L to 125 g / L, for example 50 g / L to 100 g / L, 60 g / L to 90 g / L or 65 g / L to 85 g / L. In alternative embodiments, the total washcoat loading is about 70 g / L, about 75 g / L or about 80 g / L.

[0084] The washcoat may have a pH between 4 and 7, such as between 4.5 and 6.5, preferably between 5 and 6.

[0085] The carrier coating may have a conductivity of 1 mS to 100 mS, for example 2 mS to 50 mS, 3 mS to 30 mS, 5 mS to 25 mS or 10 mS to 20 mS. In a preferred embodiment, the conductivity is 1 mS to 30 mS, for example 5 mS to 25 mS, 8 mS to 22 mS, 10 mS to 20 mS, or 12 mS to 18 mS.

[0086] Conductivity can be measured using a Cole Parmer conductivity meter at 20°C.

[0087] The viscosity of the carrier coating may be between 0 cPs and 5,000 cPs, such as 1 cPs to 3,000 cPs, 2 cPs to 2,000 cPs, 3 cPs to 1,000 cPs, 4 cPs to 500 cPs or 5 cPs to 300 cPs. In a preferred embodiment, the viscosity is between 5 cPs and 250 cPs, between 10 cPs and 200 cPs, between 15 cPs and 180 cPs, between 25 cPs and 150 cPs, between 50 cPs and 120 cPs or between 60 cPs and 100 cPs. In a more preferred embodiment, the viscosity of the carrier coating is between 5 cPs and 200 cPs, even more preferably between 25 cPs and 120 cPs, such as between 50 cPs and 100 cPs.

[0088] Viscosity can be measured at 20°C on a Brookfield RV DVII+ Extra Pro viscometer using a SC4-27 spindle at a spindle speed of 50 rpm.

[0089] Total washcoat d 90(by volume) may be between 0.1 μm and 100 μm, preferably between 0.2 μm and 50 μm, between 0.5 μm and 40 μm, between 1 μm and 30 μm, between 1.5 μm and 20 μm, between 2 μm and 10 μm, between 3 μm and 8 μm. In a preferred embodiment, the d of the total carrier coating is 90 (by volume) between 0.1 μm and 10 μm, between 0.5 μm and 9 μm, between 1 μm and 8 μm, between 1.5 μm and 7.5 μm, between 2 μm and 7 μm, between 2.5 μm and 6 μm, between 3 μm and 5.9 μm. In a more preferred embodiment, the d 90 (by volume) between 4 μm and 5.8 μm, for example about 5.5 μm.

[0090] As used herein, the term “ 90 "(by volume)" refers to the Malvern Panalytical with Aero s dispersion unit available from Malvern Panalytical Ltd., Malvern, UK. 3000 measured d 90 (by volume) Measurement results. Dispersion conditions: air pressure = 2 bar, feed rate = 65%, hopper gap = 1.2 mm. According to Malvern Set the refractive index and absorption parameters following the instructions provided in the 3000 User Manual.

[0091] Entrance front area

[0092] The inlet end front region of the monolithic article (eg, an inlet end front region as described herein) includes (eg, consists of) an inorganic oxide coating.

[0093] In a preferred embodiment, the inorganic oxide coating of the inlet end front zone is coated directly onto the monolithic article (ie, there is no intermediate layer between the monolithic article and the inorganic oxide coating).

[0094] Exit rear area

[0095] The outlet end rear region of the monolithic article (e.g., an outlet end rear region as described herein) includes a layered coating (e.g., consists of a layered coating), wherein the lower layer comprises a support coating (e.g., consists of a support coating) and the upper layer comprises an inorganic oxide coating (e.g., consists of an inorganic oxide coating).

[0096] In a preferred embodiment, the washcoat layer at the rear region of the outlet end is applied directly to the monolithic article (ie, there are no intermediate layers between the monolithic article and the washcoat layer).

[0097] In another preferred embodiment, the inorganic oxide coating of the outlet end rear zone is coated directly onto the washcoat layer (ie, there is no intermediate layer between the washcoat layer and the inorganic oxide coating layer).

[0098] In an even more preferred embodiment, the carrier coating in the rear zone of the outlet end is directly coated onto the monolithic article, and the inorganic oxide coating is directly coated onto the carrier coating (i.e., there is no intermediate layer between the monolithic article and the carrier coating, and there is no intermediate layer between the carrier coating and the inorganic oxide coating).

[0099] Method of forming a coated monolithic article

[0100] The present invention also relates to a method of forming a coated monolithic article (e.g., a coated monolithic article as described herein), the method comprising:

[0101] i) providing a monolithic product having an inlet end front region and an outlet end rear region,

[0102] ii) applying a washcoat to the outlet end rear region such that the washcoat extends from 50% to 90% of the length of the substrate from the outlet end rear region,

[0103] iii) optionally drying and / or calcining the washcoat.

[0104] iv) applying an inorganic oxide coating to the inlet end front region such that the coating extends from 50% to 100% of the length of the substrate from the inlet end front region.

[0105] A carrier coating (e.g., a carrier coating as described herein, in particular the carrier coating of step ii)) is applied to the monolithic article at the outlet end rear region of the monolithic article. The carrier coating may be applied to the outlet end rear region of the monolithic article in a single dose or multiple doses (e.g., 2, 3, 4, or 5 doses). In a preferred embodiment, the carrier coating is applied to the monolithic article in a single dose or two doses, most preferably in a single dose. When multiple doses of carrier coating are applied to the monolithic article, the same or different carrier coatings may be applied each time, preferably the same carrier coating is applied to the monolithic article.

[0106] The washcoat (e.g., washcoat of step ii)) is applied such that it extends from the outlet end rear region 50% to 90% of the length of the substrate. In a preferred embodiment, the washcoat extends from the outlet end rear region 55% to 85% of the length of the substrate, more preferably 60% to 80%, 65% to 78%, 66% to 75%, 68% to 70%, such as about 80%, about 75%, or about 70%.

[0107] The carrier coating (e.g., the carrier coating of step ii)) can be applied using any conventional method, such as an automatic inverted depositor (AID) method or a precision coating (PC) method. The AID method involves using a piston to push the carrier coating into the filter, flipping the component, and then immersing the carrier coating into the substrate wall. The PC method involves using a showerhead to apply the correct dosage amount, sucking the carrier coating into the component by gravity and / or vacuum, and immersing the carrier coating into the substrate wall. In a preferred embodiment, the carrier coating is applied to the substrate using the PC method. The carrier coating can be applied by metering the carrier coating through the outlet end rear zone, and:

[0108] i) applying a vacuum to the washcoat layer, and / or

[0109] i) applying positive pressure to the washcoat layer, and / or

[0110] iii) metering the support coating by capillary action,

[0111] to allow it to coat at least a portion of the channel with the washcoat.

[0112] The support coating may preferably be calcined prior to applying the inorganic oxide coating. Preferably, the calcining step comprises heating to a temperature of at least 200°C, preferably at least 300°C, more preferably at least 400°C, and / or a temperature of at most 600°C, preferably at most 550°C, more preferably at most 530°C. Thus, calcining preferably comprises heating to a temperature of 200°C to 600°C, preferably 300°C to 550°C, preferably 400°C to 530°C, more preferably 400°C to 500°C, even more preferably 400°C to 450°C.

[0113] An inorganic oxide coating (e.g., the inorganic oxide coating of step iv) is applied to the monolithic article that has been coated with a washcoat as described above. In a preferred embodiment, the inorganic oxide coating is applied in a spraying step. In a particularly preferred embodiment, the inorganic coating is applied only from the inlet end in a spraying step.

[0114] In one embodiment, the inorganic oxide coating is applied in a spraying step, which comprises a first spraying step, wherein the inorganic particles are sprayed as a first dry particulate aerosol to form an inorganic particle layer, and then in a second spraying step, the organosilicon resin is sprayed as a second dry particulate aerosol onto the inorganic particle layer. Thus, the inorganic particles are sprayed, and thereafter the organosilicon resin is sprayed separately onto the article coated with the inorganic particles. In a particularly preferred embodiment, the inorganic particles and the organosilicon resin are applied only from the inlet end in the spraying step.

[0115] Even more preferably, the mixture of inorganic particles and silicone resin is sprayed as a dry particulate aerosol to form the inorganic oxide coating. Thus, an intimate mixture of inorganic particles and silicone resin is applied and the adhesion of the inorganic particles to the monolithic article is enhanced when the silicone resin is calcined. In a particularly preferred embodiment, the mixture of inorganic particles and silicone resin is sprayed as a dry particulate aerosol only from the inlet end.

[0116] In the case where a mixture of inorganic particles and silicone resin is sprayed as a dry particulate aerosol to form an inorganic oxide coating (preferably, wherein the dry particulate composition consists of inorganic particles and silicone resin), the weight ratio of inorganic particles to silicone resin in the mixture is preferably greater than 0.5 (in other words, greater than 0.5:1), preferably greater than 0.7, preferably greater than 0.9, and / or less than 10, preferably less than 8, preferably less than 5. For example, the ratio may preferably be about 2 or about 3. Preferably, the ratio is 1 to 4, preferably 2 to 4.5, preferably 2.5 to 4, preferably 2.5 to 3.5, for example about 3.

[0117] The method may further include calcining the inorganic oxide coating.That is, the method includes calcining a monolithic article having inorganic particles and a silicone resin spray-coated on the porous monolithic article on gas contacting surfaces of a plurality of channels.

[0118] Preferably, the calcining step comprises heating to a temperature of at least 200° C., preferably at least 300° C., more preferably at least 400° C., and / or to a temperature of at most 600° C., preferably at most 550° C., more preferably at most 530° C. Thus, calcining preferably comprises heating to a temperature of 200° C. to 600° C., preferably 300° C. to 550° C., preferably 400° C. to 530° C., more preferably 400° C. to 500° C., even more preferably 400° C. to 450° C.

[0119] Such temperatures have been found to be most suitable for forming an effective binder that provides advantageous water resistance to the coated monolithic article. Such temperatures are particularly advantageous when the monolithic article is a catalyst article, such as a catalytic wall flow filter, because these temperatures allow the silicone resin to be calcined into crosslinked silica without negatively affecting the catalytic efficiency (i.e., without degrading the catalyst article). It is believed that linear siloxanes such as PDMS not only fail to provide the required branching to effectively bind the inorganic particles and adhere to the article, but also completely degrade to SiO 2 Temperatures in excess of 550° C. or even 600° C. may be required. Ideally, the calcination temperature is kept as low as possible to reduce the likelihood of affecting the catalytic activity of any catalyst present in the monolithic article.

[0120] The inorganic oxide coating is applied so that it extends from the inlet end front area to 50% to 100% of the length of the substrate. In a preferred embodiment, the inorganic oxide coating extends from the inlet end front area to 55% to 99% of the length of the substrate, more preferably 60% to 98%, 65% to 97%, 70% to 95%, 75% to 92%, 80% to 90%, 85% to 88%, for example about 100%, about 95% or about 90%.

[0121] Exhaust system and method

[0122] According to a further aspect, there is provided an exhaust system comprising a coated monolithic article as described herein or prepared by a method as described herein, and optionally an internal combustion engine. The internal combustion engine may be a diesel engine, a lean-burn gasoline engine, or an engine powered by liquid petroleum gas or natural gas. Preferably, the internal combustion engine is a diesel engine. The coated monolithic article may be arranged downstream of the engine to treat the exhaust gas discharged from the engine.

[0123] According to yet another aspect of the present invention, there is provided a method for treating exhaust gas, the method comprising contacting the exhaust gas with a coated monolithic article as described herein or prepared by a method as described herein.

[0124] Although the preferred embodiments of the present invention have been described in detail herein, it will be apparent to those skilled in the art that various changes may be made therein without departing from the scope of the invention or the appended claims.

[0125] The invention will now be further described with reference to the following non-limiting examples and accompanying figures.

[0126] As used herein, the singular forms "a", "an", and "the" include plural references unless the context clearly indicates otherwise. The use of the term "comprising" is intended to be interpreted as including such features but not excluding other features, and is also intended to include feature options that must be limited to those described. In other words, the term also includes the limitations "essentially consisting of..." (intended to indicate that certain additional components may be present, provided that they do not substantially affect the basic characteristics of the described features) and "consisting of..." (intended to indicate that other features may not be included, so that if these components are expressed in percentages of their proportions, these will add up to 100%, taking into account any unavoidable impurities), unless the context clearly indicates otherwise.

[0127] As used herein, the term "g / L" (grams per liter) refers to the mass of powder divided by the volume of the filter.

[0128] The foregoing detailed description has been provided by way of explanation and illustration and is not intended to limit the scope of the appended claims. Many variations of the presently preferred embodiments shown herein will be apparent to those of ordinary skill in the art and remain within the scope of the appended claims and their equivalents.

[0129] Example

[0130] Example 1

[0131] Preparation of Comparative Sample 1

[0132] A monolithic article having an inlet end and an outlet end is provided. 50% of the washcoat is metered in from the inlet end via a depositor, the article is dried in a dynamic drying oven at 115°C, and then 50% of the washcoat is metered in from the outlet end via a depositor. The article is then dried in a dynamic drying oven at 115°C and calcined at 500°C. An inorganic oxidic coating is applied to the inlet and the resulting coated article is calcined at 500°C.

[0133] Sample 2 prepared according to the present invention

[0134] A monolithic article having an inlet end and an outlet end is provided. 100% of the washcoat is metered in from the outlet end via a depositor, the article is dried in a dynamic drying oven at 115° C., and then calcined at 500° C. An inorganic oxidic coating is applied to the inlet and the resulting coated article is calcined at 500° C.

[0135] Sample 3 prepared according to the present invention

[0136] A monolithic article having an inlet end and an outlet end is provided. 50% of the washcoat is metered in from the outlet end via a depositor, the article is dried in a dynamic drying oven at 115°C, and then another 50% of the washcoat is metered in from the outlet end via a depositor. The article is then dried in a dynamic drying oven at 115°C and then calcined at 500°C. An inorganic oxidic coating is applied to the inlet and the resulting coated article is calcined at 500°C.

[0137] Example 2

[0138] The filtration efficiency was calculated for samples 1, 2 and 3. On a DPG (diesel particulate generator), the soot was measured before and after the filter and the filtration efficiency was calculated using the following equation:

[0139] Filtration efficiency = 1-(ash after filter / ash before filter)

[0140] The results are shown in Figure 1 middle.

[0141] Figure 1 It is shown that both Samples 2 and 3 have a benefit in filtration efficiency compared to Sample 1 (1.6% and 1.5%, respectively).

[0142] Example 3

[0143] Calculate the mass loading and cold flow back pressure for samples 1-3. Measure the mass loading before and after loading on the balance. 3 The cold flow back pressure was measured by measuring the pressure drop (in millibars) of the air flow at 100 °C. The results are shown in Figure 2 middle.

[0144] Figure 2 Sample 3 is shown to have the lowest cold flow back pressure. More inorganic oxide coating can be loaded onto Samples 2 and 3 compared to Sample 1, resulting in higher catalyst mass loading for similar cold flow back pressure.

Claims

1. A monolithic product, comprising an inlet end front region and an outlet end rear region, and a partitioned and layered coating, wherein the coating comprises: a) an inlet end front region comprising an inorganic oxide coating, and b) An outlet end rear region comprising a layered coating, wherein a lower layer comprises a washcoat layer and an upper layer comprises an inorganic oxide coating layer. 2 . The monolithic article according to claim 1 , wherein the inorganic oxide coating layer in the front region of the inlet end is the same as the inorganic oxide coating layer in the upper layer in the rear region of the outlet end.

3. The monolithic article according to claim 1 or claim 2, wherein the inorganic oxide coating of the inlet end front zone is directly coated onto the monolithic article.

4. The monolithic article according to any preceding claim, wherein the monolithic article is a monolithic filter, preferably a wall flow filter, and / or a catalyst article, preferably a catalytic wall flow filter.

5. The monolithic article according to any preceding claim, wherein the inorganic oxide coating comprises inorganic particles (e.g., inorganic particles comprising an aluminosilicate zeolite) and a silicone resin, preferably wherein the inorganic particles comprise an aluminosilicate zeolite selected from the group consisting of AEI, BEA, CHA and MFI.

6. A monolithic article according to any preceding claim, wherein the total inorganic oxide coating is present at a mass loading of 1 g / L to 25 g / L, such as 2 g / L to 20 g / L, preferably 3 g / L to 15 g / L.

7. The monolithic article according to any one of claims 4 to 5, wherein the ratio of inorganic particles to silicone resin in the inorganic oxide coating is 0.5:1 to 5:1, preferably 1:1 to 4:1, such as about 2:1 or 3:

1.

8. A monolithic article according to any preceding claim, wherein the washcoat comprises ceria zirconia, alumina, a noble metal selected from Pd, Pt or Rh, barium hydroxide, a rheology modifier and a C2-C6 aliphatic amino acid (e.g., 3-amino-propionic acid), and / or wherein the total washcoat loading is 35 g / L to 150 g / L, preferably 40 g / L to 125 g / L, for example 50 g / L to 100 g / L, 60 g / L to 90 g / L or 65 g / L to 85 g / L.

9. A method of forming a coated monolithic article (e.g., a coated monolithic article according to any preceding claim), the method comprising: i) providing a monolithic product having an inlet end front region and an outlet end rear region, ii) applying a washcoat to the outlet end rear region such that the washcoat extends from 50% to 90% of the length of the substrate from the outlet end rear region, iii) optionally drying and / or calcining the washcoat, iv) applying an inorganic oxide coating to said inlet end front region such that said coating extends from said inlet end front region from 50% to 100% of said length of said substrate.

10. The method according to claim 9, wherein the washcoat layer is applied to the monolithic article in a single or multiple doses, preferably in a single or two doses, at the outlet end rear region of the monolithic article.

11. A method according to claim 9 or claim 10, wherein the carrier coating is applied so that it extends from the outlet end rear region for 55% to 85%, more preferably 60% to 80%, 65% to 78%, 66% to 75%, 68% to 70%, for example about 80%, about 75% or about 70% of the length of the substrate.

12. A method according to any one of claims 9 to 11, wherein a mixture of inorganic particles and silicone resin is sprayed as a dry particulate aerosol to form the inorganic oxide coating.

13. A method according to any one of claims 9 to 12, wherein the inorganic oxide coating is applied so that it extends from the inlet end front zone to 55% to 99%, more preferably 60% to 98%, 65% to 97%, 70% to 95%, 75% to 92%, 80% to 90%, 85% to 88%, for example about 100%, about 95% or about 90% of the length of the substrate.

14. The method according to any one of claims 9 to 13, wherein the method further comprises: v) drying and calcining the inorganic oxide coating.

15. An exhaust system comprising a coated monolithic article according to any one of claims 1 to 8 or prepared by a method according to any one of claims 9 to 13, and optionally an internal combustion engine.

16. A method for treating exhaust gas, the method comprising contacting the exhaust gas with a coated monolithic article according to any one of claims 1 to 8 or prepared by the method according to any one of claims 9 to 13.

Citation Information

Patent Citations

  • Asymmetric honeycomb wall-flow filter having improved structural strength

    WO2005030365A1

  • Diesel particulate filter

    WO2011151711A1

  • Treatment of particulate filters

    WO2021028691A1

  • Method for dry coating a particulate filter

    WO2021165658A1